#   Refresher 5(2x - 3) Solving Equations 2x + 5 = x + 10 x + 5 = 10

## Presentation on theme: "  Refresher 5(2x - 3) Solving Equations 2x + 5 = x + 10 x + 5 = 10"— Presentation transcript:

  Refresher 5(2x - 3) Solving Equations 2x + 5 = x + 10 x + 5 = 10
Remember: 1. We have previously solved simple equations like the one shown and we looked at the analogy of scales in which both sides are balanced. 2x + 5 = x + 10 x + 5 = 10 x = 5 2x + 5 x + 10 2. We have previously expanded single brackets as shown below. 5(2x - 3) means 5 x (2x - 3) = 10x - 15 + x + = + + x - = - - x + = - - x - = + 3. We are familiar with the rules for signs when multiplying. Unlike signs give a negative Refresher We now need to know that the same rules apply for division.

Ex Q’s 2 Brackets Solving Equations 2(x + 1) = x + 5
Example Questions With Brackets 2(x + 1) = x + 5 Example Question 1: solve 3(x - 1) = 2(x + 7) Example Question 2: solve 2x + 2 = x + 5 3x - 3 = 2x + 14 x + 2 = 5 x - 3 = 14 x = 3 x = 17 3(x - 2) - 2(x + 1) = 5 Example Question 3: solve 7(x - 2) - 4 = 2(x + 2) Example Question 4: solve 3x x - 2 = 5 7x = 2x + 4 x - 8 = 5 7x = 2x + 4 Ex Q’s 2 Brackets x = 13 5x = 4 5x = 22 x = 4.4

Questions 2 Solving Equations (a) 8(x + 1) = 2(x + 16)
Solve the following equations (a) 8(x + 1) = 2(x + 16) (b) 10(x + 1) = 7(x + 4) (c) 6(x - 5) = 5(x - 4) (d) 3(x + 2) = 2(x - 1) (e) 7(x - 2) - 3 = 2(x + 2) (f) 3(x + 1) + 2(x + 2) = 10 (g) 5(x - 3) + 3(x + 2) = 7x (h) 2x - 3(x + 2) = 2x + 1 Questions 2

Worksheets Questions 1 Questions 2 (a) 6x + 8 = 2x - 12
(b) 5x - 4 = x (c) 9 + 3x = x (d) 3 - 7x = 7 + x (e) 2x - 7 = x (f) 9x + 25 = 5 + x (g) 7x + 8 = x (a) 8(x + 1) = 2(x + 16) (c) 6(x - 5) = 5(x - 4) (d) 3(x + 2) = 2(x - 1) (b) 10(x + 1) = 7(x + 4) (e) 7(x - 2) - 3 = 2(x + 2) (f) 3(x + 1) + 2(x + 2) = 10 (g) 5(x - 3) + 3(x + 2) = 7x (h) 2x - 3(x + 2) = 2x + 1 Questions 1 Questions 2 Worksheets

Download ppt "  Refresher 5(2x - 3) Solving Equations 2x + 5 = x + 10 x + 5 = 10"

Similar presentations